Ethical Study of Youth Addicted to Porn, Masturbate, Orgasm (PMO) in the Gmim Tasik Wangurer Congregation, Bitung Region VIII: Kajian Etis Terhadap Pemuda Yang Kecanduan Porn, Masturbate, Orgasm (PMO) Di Jemaat Gmim Tasik Wangurer Wilayah Bitung VIII - Morshe Everly Lumansik; Friedrich Feliks Bimbanaung; James Edward Lalira (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
PMO addiction (Pornography, Masturbation, and Orgasm) is a serious issue that negatively impacts mental, physical, and spiritual health, particularly for the youth in the GMIM Tasik Wangurer congregation in the Bitung VIII region. This study aims to examine the issue of PMO addiction from a Christian ethical perspective and provide appropriate treatment recommendations. The urgency of this research lies in the widespread impact of PMO addiction on individual and church community life, as well as the need for a holistic approach that aligns with Christian values for addressing this issue. The research method includes literature review, in-depth interviews with involved youth, and consultations with theologians and mental health experts. The results of the study indicate that PMO addiction contradicts Christian ethical principles such as holiness, self-control, love, and the calling to live a holy life. The implementation of the research findings includes faith-building through pastoral counseling services, Bible study and prayer, and mentoring programs; education and awareness through seminars, training, and support groups; as well as positive direction through talent development and character building. By applying these measures, it is hoped that youth experiencing PMO addiction can recover and lead lives that align with their calling as holy and pleasing children of God